The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1413-81232008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Georeferenced data in epidemiologic research

Abstract: Resumo Neste artigo, faz-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 72 publications
0
31
0
2
Order By: Relevance
“…Our results suggested that the annual incidence rates were fluctuated considerably, with the peak incidence rate in 2008. The reasons for spatial clustering of disease rates may put down in the heterogeneous allotment of essential factors such as crowding, social inequality, and access to health services or environmental characteristics [49-51]. …”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that the annual incidence rates were fluctuated considerably, with the peak incidence rate in 2008. The reasons for spatial clustering of disease rates may put down in the heterogeneous allotment of essential factors such as crowding, social inequality, and access to health services or environmental characteristics [49-51]. …”
Section: Discussionmentioning
confidence: 99%
“…The biomedical and public health literature on geographic information systems (GIS) and spatio-temporal analyses features a large number of research papers mentioning or addressing location privacy, e.g., [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. A must-read paper (not specifically health-related) dating back to 1994 [29] shows how chronic privacy issues are in GIS research.…”
Section: Research Literature: Location Privacy Concerns and Solutionsmentioning
confidence: 99%
“…This information is required by public health authorities making immunization policies, health care practitioners making recommendations about vaccination, and individuals making health decisions for themselves and their families. Maps are one of the most effective ways to rapidly convey information about global issues [20]. However, maps can only display a limited amount of information, and complex decisions must be made about what information to display and how best to display it.…”
Section: Introductionmentioning
confidence: 99%